Lens development and disorders - clinical diagnosis and treatment - Lloyd, Chris (Henry Stewart Talks, 2016)
Congenital and developmental lens anomalies including spherophakia, lenticonus and lentiglobus, Congenital cataract and it’s management, Lens abnormalities associated with persistent fatal vasculature (PFV), Dislocated lenses (Ectopia Lentis): aetiology and management